Integrasi Pertahanan Siber dalam Sistem Pertahanan dan Keamanan Rakyat Semesta (Sishankamrata): Analisis Komparatif dengan Amerika Serikat, Estonia, dan Singapura - Wisanggeni Sholata Sya; Herlina Tarigan; Susanto Susanto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Modern conflict has evolved into the cyber domain as part of hybrid warfare, demanding a reinterpretation of the Sishankamrata (Total People's Defense and Security System) doctrine to encompass the digital realm. This study aims to analyze the integration of cyber defense into the Sishankamrata framework using a literature review and comparative analysis with the cyber defense strategies of the United States, Estonia, and Singapore. The results indicate that the implementation of Sishankamrata in the cyber domain faces challenges regarding inter-institutional synergy and unclear operational roles for the Reserve and Support Components. Based on the comparative analysis, Estonia's Cyber Defence Unit model and Singapore's Digital Defence pillar are identified as the most effective blueprints for Indonesia to mobilize civilian experts and enhance social resilience. This study recommends that the government formalize "Digital Defense" as an integral pillar of Sishankamrata, establish a Cyber Reserve Component consisting of expert civilian volunteers, and strengthen legal frameworks and public digital literacy as a form of state defense